The Effect of Wintering with Wooden Hives with Differently Materials Manufactured Bottom on Bee Covered Frames and Hive Weights - Karlidag, Semiramis; Seker, Ibrahim; Koseman, Abdurrahman; Akyol, Abuzer (Univ Namik Kemal, 2021)
Some problems that do not cause death in spring and summer are in winter, colony losses occur mostly during wintering and the fact that winter losses still cannot be reduced to below 8-10% requires new researches in beekeeping. The use of different hive types suitable for the conditions of the beekeeping region affects the health and life force of the bees as well as the amount of honey and other bee products to be obtained. This research was carried out to determine the effects of wintering honeybee (Apis mellifera L.) colonies on beehive frame numbers and hive weights in wooden based (WB) and screened-pollen trapped plastic based (SPTPB) wooden hives. The current research was carried out in the trionti University Apiculture Development Application and Research Center. A total of 21 honeybee colonies were used as bee material in the study. Colonies were wintered in 12 WB and 9 SPTPB wooden hives. While the wintering ability was calculated as 42.03% in WB hives and 47.27% in SPTPB wooden hives, the colony loss in all beehives was determined as 55.35%. Differences between the number of bee frames before and after wintering in each hive type were statistically significant at different levels (p = 0.041-0.007). It was determined that the wooden hives and SPTPB wooden hives retain 51.60% and 51.89% respectively of their weight at the beginning of the winter. In this study, differences between WB and SPTPB wooden hive types were not found statistically significant in terms of hive weights both before and after wintering (p>0.05). However, differences among the beehive weights of each beehive type before and after wintering were found statistically significant at different levels (p = 0.028-0.008). As a result, it was concluded that both types of hives can be preferred in beekeeping by considering other yield characteristics, cost, longevity and health conditions.
Farkli materyallerden yapilmiş tabana sahip ahşap kovanlarla kişlatmanin arili çerçeve sayisi ve kovan a?irli?ina etkisi
Keywords: Wooden hive; Bee frame; Honeybee (Apis mellifera L.); Colony; Hive weight